The repossession - Hawksmoor, Sam (London: Hodder Children's Books, 2012)
34 kids missing. Vanished without a trace. Believing she is possessed, Genie Magee's mother has imprisoned her all summer encouraged by the sinister Reverend Schneider. Beautiful Rian, love of her life, sets her free, but their escape washes them up at Marshall's remote farmhouse downriver. Why are there newspaper clippings of missing kids pinned to his bathroom wall? And should they believe his stories about the experiments at the Fortress, an underground research station nearby? Genie meets Denis. Missing two years now, but not grown an inch. Rian is haunted by Renee, who insists she's not actually dead. Soon they discover the terrible truth about Reverend Schneider and worse, Genie is next ... and Rian can't do a thing to prevent it. The Repossession is just the beginning
Keywords: Young adult fiction